Preventing falls with Tai Ji Quan: A public health perspective - Stevens, Judy A. (J Sport Health Sci, 2014)
Falls among people aged 65 and older are a significant public health problem and one that is expected to increase as the population ages. Randomized controlled trials have demonstrated that Tai Ji Quan can reduce falls and associated injuries among older adults. In this paper, we describe how Tai Ji Quan community programs are being utilized by public health and aging services organizations to reduce older adult falls. We conclude that, to have a population-level impact on reducing falls and improving the health of older adults, Tai Ji Quan interventions must be translated into community programs that meet the needs and abilities of older adults. These programs must be adapted to fit into existing community structures, disseminated through multiple delivery channels, adopted and implemented broadly by organizations, and institutionalized to ensure sustainability.